Enhancing Land Registration Systems Using Blockchain Technology: A Case Study of Adama City - Dagnie, Arega (ASTU, 2025)
Efficient and transparent land registration systems are critical for secure land tenure. This study aims to investigate the potential of blockchain technology to improve the land registration system in Adama City. Data were gathered from both primary and secondary sources. Primary data included semi-structured interviews with government officials, land administrators, real estate agents, and blockchain experts, as well as focus group discussions with local residents and landowners. The study employed a structured data processing and analysis method to ensure accurate integration of land registry data into a blockchain system. Initial preprocessing involved cleaning, verifying, and standardizing data from multiple sources to meet blockchain compatibility standards. The study demonstrated the effectiveness of blockchain technology in ensuring transparent, traceable, and immutable land registry transactions. Ownership analysis across 19 parcels revealed dynamic participation, with parcels like 42, 47, 49, and 60 each undergoing three ownership changes the highest in the dataset. Network analysis identified central actors such as Hanna, Jemila, and Girma, who engaged in over five transactions each, indicating strong market influence. Spatial analysis showed that parcels in the central region experienced the highest transaction density, with up to three transactions per parcel. The blockchain audit, covering 6 blocks and recording 24 transactions, confirmed the integrity and chronological traceability of all changes. These findings underscore blockchain’s potential to enhance land governance by improving accountability, reducing fraud risk, and providing a secure, auditable framework for land administration. The study revealed that blockchain technology significantly enhances public trust and access to land information in Adama City by providing a transparent, immutable, and decentralized system that reduces corruption and enables real-time, user-friendly access to land records. The system demonstrated efficient recording of ownership changes, prevention of tampering, and clear visualization of land transfer patterns, supporting fair and accountable land administration.
Keywords: Blockchain, Land Registry, Land Transactions, Transparency, Ownership Traceability